Determination of the antioxidant capacity of pineapple peel powder extract by applying different extraction techniques (Research, Society and Development, 2021)
The pineapple is one of the most cultivated and appreciated fruits in Brazil, so that along with the increase of its processing, comes the increase of its residues that in most cases are discarded, despite having relevant nutrients. The objective of the present work was to study the utilization of the pineapple peel from the Submédio do Vale do São Francisco to obtain oil or extracts with antioxidant capacity through the use of low pressure extraction techniques, such as the Soxhlet system, maceration and ultrasound-assisted extraction, using organic solvents of different polarities. Afterwards, the yield of the extracts obtained was verified, the extraction with ethanol showed the best results. For the total phenolic content (TFT) the maceration technique stood out with 12723.52 mg/g, and to determine the antioxidant activity (AA), the ABTS and DPPH radicals were used, with respective results of 0.04084 and 0.03859 mMTrolx/g by the ethanol maceration method. Thus, it can be concluded that the pineapple peel can be a raw material of significant potential in the preparation of an extract with antioxidant characteristics.